2002
DOI: 10.1161/01.cir.0000016050.79810.18
|View full text |Cite
|
Sign up to set email alerts
|

Bucindolol Displays Intrinsic Sympathomimetic Activity in Human Myocardium

Abstract: Background-Most clinical studies have shown that ␤-adrenergic receptor antagonists improve long-term survival in heart failure patients. Bucindolol, a nonselective ␤-receptor blocker, however, failed to reduce heart failure mortality in a recent large clinical trial. The reasons for this failure are not known. Bucindolol has partial agonist properties in rat myocardium, but whether it has agonist activity in human heart is controversial. To address this, we measured the ability of bucindolol to increase cAMP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 44 publications
5
34
0
Order By: Relevance
“…Bucindolol induced rapid and prominent phosphorylation of the human ␤ 1 -AR. Together with recent data demonstrating cAMP stimulation in response to bucindolol, 15 this clearly classifies bucindolol as a partial agonist at the human ␤ 1 -AR.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Bucindolol induced rapid and prominent phosphorylation of the human ␤ 1 -AR. Together with recent data demonstrating cAMP stimulation in response to bucindolol, 15 this clearly classifies bucindolol as a partial agonist at the human ␤ 1 -AR.…”
Section: Resultssupporting
confidence: 69%
“…To elucidate whether the variability in the inotropic effects of bucindolol in previous studies on human myocardium [12][13][14][15] was due to different sensitization states of ␤-ARs, 16 failing myocardium was pretreated with isoproterenol, metoprolol, or vehicle for 90 minutes. The baseline force of contraction was not different among the 3 groups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is well possible that such firmly bound carvedilol may mask increases in β-AR. On the other hand, for bucindolol, several authors have found that it exerts partial intrinsic sympathomimetic activity (ISA) in the human myocardium (Maack et al 2000(Maack et al , 2003Andreka et al 2002). Previous studies had shown, however, that β-AR blockers with intrinsic sympathomimetic activity decrease cardiac β-AR density (Michel et al 1988), and this would explain the lack of cardiac β-AR up-regulation during chronic bucindolol treatment.…”
Section: Effects On β-Adrenoceptor Densitymentioning
confidence: 99%
“…13 There has been controversy about bucindolol possessing ISA on the basis of evidence of this property in functioning rat myocardium 14 and perhaps in nonfunctioning human myocardial tissue cultures. 15 However, three independent studies in functioning isolated human nonfailing or failing human myocardial preparations have demonstrated no ISA for bucindolol, even under conditions of augmented signal transduction. 16 -18 Moreover, in the most sensitive method of ISA detection, Holter Monitoring of 24-hour heart rate, xamoterol, and celiprolol demonstrate ISA, but bucindolol does not.…”
mentioning
confidence: 99%